The Nature of Software Education in Fashion Design: Growth, Sustainability, and Challenges - Van , Ha Tu; Tung, Nguyen Mau; Chien, Nguyen Thi My; Thuc , Huynh Van (Cadernos de Educação Tecnologia e Sociedade, 2024)
The nature of software education in fashion design refers to the application of software tools to support and enhance the processes of creativity, design, and garment production. In the fashion industry, software not only helps optimize design steps, from prototyping and sketching to 3D simulations, but also assists in managing production, tracking trends, analyzing markets, and streamlining manufacturing processes. This study explores how the principles of advanced software technology education are driving the modernization of the fashion design industry. In the context of rapidly advancing digital technologies, tools such as 3D design, virtual reality (VR), artificial intelligence (AI), and machine learning (ML) are transforming the ways fashion is designed, produced, and marketed. The research highlights the benefits of these technologies, including time and cost efficiency, improved product quality, and the ability to quickly respond to market demands. It also addresses the challenges involved and proposes strategies to promote sustainable development within the industry. The goal is to provide a comprehensive and insightful understanding of how software technology education influences fashion design, ultimately supporting innovation and driving operational efficiency in this dynamic field.